Główne zmiany uwarunkowań rozwoju przedsiębiorczości w Polsce - Dylak, Małgorzata (Main Changes in Conditioning of the Enterprise's Development in Poland, 2006)
The paper presents basic changes in conditioning of the companies' activity in Poland, which came within last years. These transfigurations had first and foremost the economic and institutional character and they caused barriers of entrepreneurs' activity to be levelled to a considerable degree.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 67-73